Ultrastrong nanocrystalline stainless steel and its Hall-Petch relationship in the nanoscale. (October 2018) - Yin, Fei; Cheng, Gary J.; Xu, Rong; Zhao, Kejie; Li, Qiang; Jian, Jie; Hu, Shan; Sun, Shaoheng; An, Licong; Han, Qingyou
Abstract: An ultrastrong nanocrystalline stainless steel with a yield strength of 2.0 GPa was reported and the Hall-Petch equation of the stainless steel in the nanoscale was determined. The effects of the grain refinement and element segregation on the mechanical behaviors of the nanocrystalline stainless steel were analyzed and discussed. The validated Hall-Petch equation for the stainless steel in the nanoscale regime could provide a guideline for Hall-Petch strengthening of the stainless steel with grain refinement. Graphical abstract: Unlabelled Image